2021
DOI: 10.2174/1570159x18666200507082311
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosol as a Neuroprotector: Strong Effects of a “Weak” Antioxidant

Abstract: : The use of neuroprotective agents for stroke is pathogenetically justified, but the translation of results of preclinical studies of neuroprotectors into clinical practice has been a noticeable failure. One of the leading reasons for these failures is the one-target mechanism of their activity. p-Tyrosol (Tyr), a biophenol, is present in a variety of natural sources, mainly in foods, such as olive oil and wine. Tyr has a wide spectrum of biological activity: antioxidant, stress-protective, anti-inflammatory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 142 publications
1
16
0
1
Order By: Relevance
“…In an in vitro incubation study with human fecal slurry, cinnamylalcohol, tyrosol, and hydroquinone were identified as the main phenolic metabolites [ 168 ]. Tyrosol is able to penetrate the BBB and has shown potent neuroprotective and neuroregenerative activities in vitro and in animal studies [ 244 ], and hydroquinone has shown protective effects against transient focal cerebral ischemia in rats [ 245 ], indicating the neuroprotective potential of these gut microbial R. rosea metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…In an in vitro incubation study with human fecal slurry, cinnamylalcohol, tyrosol, and hydroquinone were identified as the main phenolic metabolites [ 168 ]. Tyrosol is able to penetrate the BBB and has shown potent neuroprotective and neuroregenerative activities in vitro and in animal studies [ 244 ], and hydroquinone has shown protective effects against transient focal cerebral ischemia in rats [ 245 ], indicating the neuroprotective potential of these gut microbial R. rosea metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Prior to HPLC analysis, polyphenols were extracted from olive oil by US-LLE using methanol and hexane [ 53 ]. HTyr [ 71 , 72 ] and Tyr [ 73 ] are phenolic compounds specific to olive oil, while cinnamic acid [ 74 ], apigenin [ 75 ], and pinoresinol [ 76 ] are widespread and found in a great number of plants. All of these compounds are well known for their bioactive properties, such as antioxidant and antitumor activities, in addition to many others [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…(Cimmino et al, 2017), Diaporthella cryptica (Cimmino et al, 2018). Moreover, several studies have also reported tyrosol from the bioactive extracts of endophytic Colletotrichum (Colletotrichum gleosporoides, Colletotrichum crassipes) (Anisha and Radhakrishnan, 2017;Masi et al, 2018;Plotnikov and Plotnikova, 2020). However, the report of its isolation from C. coccodes is limited.…”
Section: Discussionmentioning
confidence: 99%